2012
DOI: 10.1007/s00421-012-2561-z
|View full text |Cite
|
Sign up to set email alerts
|

Knee extensor strength differences in obese and healthy-weight 10-to 13-year-olds

Abstract: The purpose of this study was to investigate if obese children have reduced knee extensor (KE) strength and to explore the relationship between adiposity and KE strength. An observational case-control study was conducted in three Australian states, recruiting obese [N = 107 (51 female, 56 male)] and healthy-weight [N = 132 (56 female, 76 male)] 10- to 13-year-old children. Body mass index, body composition (dual energy X-ray absorptiometry), isokinetic/isometric peak KE torques (dynamometry) and physical activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
2
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 28 publications
3
46
2
8
Order By: Relevance
“…Indeed, it is likely that the level of voluntary torque produced during MVC partly accounted for the greater peripheral fatigue and earlier exhaustion in obese girls. As expected (Tsiros et al 2013), obese girls produced higher absolute KE torque than their normal weight counterparts. Interestingly, we demonstrated here that this higher force production capacity was positively correlated to the peripheral fatigue development (i.e., Qtw pot decrement).…”
Section: Peripheral Mechanismsmentioning
confidence: 70%
See 1 more Smart Citation
“…Indeed, it is likely that the level of voluntary torque produced during MVC partly accounted for the greater peripheral fatigue and earlier exhaustion in obese girls. As expected (Tsiros et al 2013), obese girls produced higher absolute KE torque than their normal weight counterparts. Interestingly, we demonstrated here that this higher force production capacity was positively correlated to the peripheral fatigue development (i.e., Qtw pot decrement).…”
Section: Peripheral Mechanismsmentioning
confidence: 70%
“…Despite this lack of consensus regarding the rate of fatigue development in obese people, we suggest that obese individuals could fatigue to a greater extent than their normal weight counterparts because of (i) their higher absolute strength/power capacity (Abdelmoula et al 2012;Maffiuletti et al 2013;Tsiros et al 2013) and (ii) their potentially higher amount of fast-fatigable muscle fibers (Kriketos et al 1997;Wade et al 1990). Indeed, it has been shown that the higher neuromuscular fatigue of healthy men vs. women was no longer observed when subjects were matched for absolute MVC force (Hunter et al 2004), suggesting that the higher the MVC force, the higher is the muscle fatigue.…”
Section: Introductionmentioning
confidence: 95%
“…In obese girls and boys, higher absolute KE force values have been reported compared to non-obese (19)(20)(21)(22). This has been ascribed to a greater total fat-free mass in obese (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This has been ascribed to a greater total fat-free mass in obese (e.g. (22)), but also to a higher relative force (i.e. normalized to segmental muscle mass; (19)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation